The Role of Organizational Adaptation in Achieving Quality in Higher Education A Case Study at the University of Sulaimani during the Financial Crisis 2016-2019 - Solav Ezaldin al-Dalwi; Soza Mohammed Qadir; Hawar Fatah Karim; Sakar Aziz Rashid (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The current research sought to show the correlation and impact between organizational adaptations of lecturers during crises in achieving the quality of higher education at the University of Sulaymaniyah in the Kurdistan Region of Iraq, To achieve this, a hypothetical scheme has been prepared that includes research variables, in addition to formulating a number of main and sub-hypotheses, And where the researchers used the electronic questionnaire for this purpose as a main tool for collecting data, As it was sent twice through the official e-mail to most of the lecturers at the University of Sulaymaniyah, who number about (1800) teaching staff, and only 102 copies of which were valid for statistical analysis were received and all of its paragraphs were answered by them, And who spent many years delivering lectures at the colleges of the University of Sulaymaniyah, especially during the financial crisis that the Kurdistan Region was exposed to recently, Which extended from the beginning of the year 2016 to the beginning of the current year 2019, as its results negatively affected the living life of employees of the state departments in the Kurdistan Region in general, lecturers and employees of educational institutions in particular, including universities, and this situation lasted for about three years, Accordingly, Sulaymaniyah University was chosen as the research community, and a number of statistical methods were used to test the hypotheses of the research. Because of the limited studies that dealt with the relationship and influence between these variables in the Iraqi environment in general and the Kurdish environment in particular within the limits of the researchers’ knowledge, so the current research dealt with these variables within a holistic framework, In general, the research attempted to answer the following question: What is the nature of the role played by organizational adaptation among a sample of university members at the University of Sulaymaniyah during crises in achieving the quality of higher education in that university? Accordingly, the research reached a set of conclusions, the most important of which are: The organizational adaptation of the university members at the University of Sulaymaniyah during crises plays a major role in achieving the quality of higher education in the researched university, by describing and analyzing the dimensions of both variables, Based on this, the researchers presented a set of proposals consistent with these conclusions.